Successful prevention of tunneled central catheter infection by antibiotic lock therapy using cefazolin and gentamicin - Silva, T. N. V. [UNESP]; Mendes, M. L. [UNESP]; Abrão, Juliana Maria Gera [UNESP]; Caramori, J. T. [UNESP]; Ponce, Daniela [UNESP] (Springer Nature, 2012)
Catheter-related bacteremia (CRB) is one of the various complications related to hemodialysis (HD). As a result of this high rate of infection, the antibiotic lock technique (ALT) has been recommended to prevent CRB. However, adverse effects of ALT such as increased emergence of strains resistant to antibiotics and increased mechanical dysfunction catheter were poorly evaluated. We prospectively evaluated the efficacy of catheter-restricted filling using an antibiotic lock solution in preventing CRB. A total of 233 HD patients requiring 325 new tunneled catheters while waiting for placement and maturation of an arteriovenous fistula or graft were enrolled in this study. Patients with a tunneled catheter were assigned to receive either an antibiotic-heparin lock solution (antibiotic group: cefazolin 10 mg/ml, gentamicin 5 mg/ml, heparin 1,000 U/ml) or a heparin lock solution (no-antibiotic group: heparin 1,000 U/ml) as a catheter lock solution during the interdialytic period. The present study aimed to assess the efficacy of ALT using cefazolin and gentamicin in reducing CRB in patients undergoing HD with tunneled central catheter and to identify its adverse effects. CRB developed in 32.4 % of patients in the no-antibiotic group and in 13.1 % of patients in the antibiotic group. CRB rates per 1,000 catheter-days were 0.57 in the antibiotic group versus 1.74 in the no-antibiotic group (p < 0.0001). Kaplan-Meier analysis also showed that mean CRB-free catheter survival was significantly higher in the antibiotic group than in the no-antibiotic group (log-rank statistic 17.62, p < 0.0001). There was statistically significant difference between the two groups in causative organisms of CRB, with predominance of negative culture in both groups, but this prevalence was higher in ALT group (57.9 vs 90.1 %, p < 0.0001), and the two groups also were different in prevalence of gram-positive bacteria as causing organisms (ALT group 21.05 vs = 0 % in control group, p < 0.0001). There was no statistically significant difference between the two groups in drug-resistant germs. There were statistically significant differences between the two groups in the catheter removal causes, with higher rate of infectious cause in control group (12.32 vs 2.22 %, p < 0.0001) and mechanical cause in ALT group (28.26 vs 37.78 %, p < 0.0001). The results suggest that ALT may be a beneficial means of reducing the CRB rate in HD patients with tunneled catheter, without association between ALT and emergence of strains resistant. However, mechanical complications were more prevalent in antibiotic group. Further studies are required to determine the optimal drug regimen, concentrations for ALT, and its adverse effects. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Antibiotic lock technique; Catheter-related bacteremia; Hemodialysis; Tunneled central catheter